El maltrato psicológico infantil y su influencia en el comportamiento de los niños y niñas del primer año de educacion basica de la Escuela Fiscal Mixta Héroes del Cenepa y del Jardín de Infantes Olimpia Cárdenas de Rosales de la ciudad de Machala, en el periodo 2012-2013. - Rivas Sánchez, Mónica Doris (2013)
Child abuse is the set of chronic, persistent and very destructive manifestations that threaten the normal psychological development of the child. These behaviors include insults, contempt, rejection, indifference, confinement, threats, mockery, criticism or isolation that cause, or can cause, deterioration in the child's emotional, social and intellectual development. This type of abuse, causes that in the first years of the child, he can not develop attachment adequately, and in later years he feels exclusive of family and social environment, affected his self-esteem and his social skills.